Protease, Lipase and Amylase Activities in Barred Loach, Nemacheilus Fasciatus C.V. - Susilo, Untung; Rachmawati, Farida Nur (Jurnal Biodjati, 2020)
Barred loach is wild fish in which there is no information related to its enzymatic digestive capacity yet. Therefore research on this subject needs to be conducted. The spectrophotometry method was used to study protease, lipase, and amylase activities in barred loach. The study used 89 fish with an average weight of 3.61 ± 0.26g, and 1.68 ± 0.21g. The results showed that pH 7.0 was the highest protease activity. Similarly, lipase activity found between pH 7.0 and pH 8.1. Still, the amylase activity found to be high at pH 8.1. Protease activity also found to be high in the posterior intestine than in the hepato-pancreas and anterior intestine. Lipase and amylase activities did not found differences between hepato-pancreas, anterior intestine, and posterior intestine. In conclusion, the protease, lipase, and amylase activities of barred loach found along the gastrointestinal tract in both large and small fish, which shows that barred loach can digest protein, fat, and carbohydrates in diets better.